Assessing the impact of workforce diversity on employee perfomance : Astudy of the food and beverafe retail industry in Malaysia - Harshini, Sandrasegar (2024)
Diversity in the workforce has been recognized as one of the key competencies that give firms an advantage over their competitors. Hiring and involving workers from a range of diverse backgrounds and identities within a business is known as workforce diversity. The most often varied demographic factors found in the workforces of many firms are age diversity, gender diversity, and ethnic diversity. Thus, this study focuses on assessing the impact of workforce diversity on employee performance in terms of age, gender, and ethnicity. Positive effects arise from effectively managing workforce diversity, while it could have unfavorable effects if not handled well. This study was conducted with employees from a few cafés in selected food and beverage retail industry in Malaysia and used a self-administered questionnaire to gather data from employees. The Cronbach’s alpha of the questionnaire items indicated strong internal consistency and reliability. The empirical relationship between age, gender, and ethnicity of the employees and their performance was computed using the Software Package for Social Science (SPSS). The analysis reveals that age, gender, and ethnicity diversity have a significant impact on employee performance in the food and beverage retail industry in Malaysia